Aryloxide-Promoted Catalyst Turnover in Lewis Base Organocatalysis - Hartley, Will C.; O’Riordan, Timothy J. C.; Smith, Andrew D. (Synthesis, 2017)
This short review highlights select examples of enantioselective Lewis base promoted reactions that use tertiary amine (cinchona alkaloids, isothioureas, and DMAP/PPY derivatives) or NHC catalysts and employ aryloxide-promoted catalyst turnover from an acyl ammonium or azolium intermediate. This review focuses on the range of strategies that have been developed within this area, and discusses their evolution and context.1 Introduction2 Phenols as Additives To Promote Catalyst Turnover2.1 NHC Catalysis with α-Functionalised Aldehydes and Phenols2.2 Enantioselective Fluorination with Aryloxide-Promoted Catalyst Turnover3 In Situ Catalytic Generation Of Aryloxide3.1 Aryloxide-Promoted Turnover Generated from an Electrophilic Polyhalogenated Quinone: Overview3.2 Aryloxide-Promoted Catalyst Turnover Generated from an α-Aryloxyaldehyde or Aryl Ester Starting Material: Overview4 Summary and Outlook
Keywords: Lewis base catalysis; catalyst turnover and release; aryloxide; isothiourea; NHC; tertiary amines